Equilibrium Studies for Adsorption of Zn2+ on to Acid Treated Kikuyu Grass Pennisetum Clandestinum Biomass - Murithi, Genson; wa-Thiong’o, Karanja; Wachira, Jackson M. (My University, 2016)
The feasibility of using Pennisetum clandestinum biomass as low-cost adsorbent for the removal of Zn2+ was investigated in batch studies. The Freundlich, Langmuir,Dubinin Raduskevich and Temkin adsorption isotherms were used to analyze the experimental data. The kinetic analyses of the adsorption processes were performed using pseudo-first order and pseudo-second order kinetic models. The Langmuir isotherm adequately described the adsorption of Zn2+ onto the material. The maximum adsorption capacity max q was found to be 25.34 Mg/g. The Langmuir dimensionless constant, separation factor (RL) was between 0<RL<1, indicating favorable adsorption. The heat of adsorption (kJmol-1) obtained were generally somewhat low, indicating physisorption of Zn2+ to the adsorbates. For the kinetic studies, the pseudo -second order model suitably described the removal of Zn2+ by Pennisetum clandestinum biomass.
Keywords: Adsorption; Isotherms; Kinetics; Pennisetum clandestinum biomass; Zinc (II) ions